Turning Water Abundance Into Sustainability in Brazil - Farjalla, Vinicius F.; Pires, Aliny P. F.; Agostinho, Angelo A.; Amado, André M.; Bozelli, Reinaldo L.; Dias, Braulio F. S.; Dib, Viviane; Faria, Bias M.; Figueiredo, Andrea [UNESP]; Gomes, Eli A. T.; Lima, Ângelo J.R.; Mormul, Roger P.; et al. (Frontiers, 2021)
Brazil is a powerhouse in terms of water resources, which are instrumental to the country’s transition to sustainability. However, to realize this potential, substantial management and conservation hurdles must first be overcome. We propose a novel strategy for the use, management, and conservation of Brazilian water resources. Our approach recognizes the spatial heterogeneity of water abundance and is based on a multisectoral perspective, including energy, food, sanitation, and environmental conservation. The main recommendations are to adopt low-cost local and subnational solutions and to design policy mixes, both based on the logic of the nexus water-food-energy-ecosystem. We offer as examples programs that 1) increase cistern infrastructure in drylands, 2) use constructed wetlands to improve sewage treatment in small cities and vulnerable areas, 3) turn the focus of conservation to aquatic ecosystems, 4) stimulate the adoption of small hydrokinetic turbines for energy generation in sparsely populated river-abundant regions, such as the Amazon Region, 5) diversify the matrix of renewable energy sources by combining hydropower with biomass and wind energy generation, and 6) mixes policies by integrating multiple sectors to improve regulation, use and management of water resources, such as the Brazilian “Water for All” Program. By following these recommendations, Brazil would align itself with the goals established in international agreements and would turn its abundance of water resources into development opportunities.
Keywords: constructed wetlands; hydropower; nexus approach; policy mixes; protected areas; water resources